(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
Lactic acid bacteria have for years constituted a heterogeneous group of bacteria. They are microorganisms used in the food industry for the production of fermented products. The objective of this work was to technologically evaluate two strains of lactic acid bacteria isolated from raw cow’s milk. The research was divided into 3 phases 1) isolation and selection, 2) evaluation of the phenotypic characteristics of the selected lactic acid bacteria and 3) technological evaluation of the strains as starter cultures at the laboratory level. The methodology used consisted of the application of methods, techniques and standards under which the isolated strains were isolated, characterized and evaluated, resulting in the formulation of 3 starter cultures (LSF strain, LMM strain and the combination of both LSF-LMM). Regarding the results obtained, it was observed that for the lactic acid variable (g/l) evaluated, both strains and their combination presented the same behavior, that is, they can be used to replace the commercial strain that is generally used for the production of yogurt, even though they have a low production of lactic acid. Regarding pH, the combination of the LSF – LMM strains achieved a decrease in pH from 6.05 to 4.29 after 24 hours. This leads to confirmation that of the isolated strains used as starter cultures, at least one was different in terms of the characteristics of the two formulations developed.